Postharvest Interventions Involving Novel Ethylene Antagonists, Ozone and AiroFresh® in Regulating Ethylene and Maintaining Quality of Apple and Pear Fruits - Tokala, Vijay Yadav (Curtin University, 2019)
Ethylene plays a key role in the ripening process, postharvest senescence and deterioration of fruit. The efficacy of new ethylene antagonists, 1H-cyclopropabenzene and 1H-cyclopropa[b]naphthalene, to manage ethylene effects as well as maintain fruit quality in apple and pear during cold or controlled atmosphere storage with or without ozone or AiroFresh® was investigated. Fumigation or dip treatment with 1H-cyclopropabenzene and 1H-cyclopropa[b]naphthalene effectively inhibited ethylene action, retarded ethylene production and maintained quality of apple and pear fruit.